Differenciální diagnostika pleurálních výpotků. Zkusenosti z klinické studie 1986-1990 - Marel, M; Stastný, B; Melínová, L; Svandová, E (Casopis lekaru ceskych, 1991)
In a group of 171 patients with pleural effusions included in a perspective study at the Second Clinic for Tuberculosis and Respiratory Diseases in Prague in 1986-1990, the authors evaluated the asset of examination methods for the diagnosis of different types of effusions. They compared differences between the group of patients with effusions associated with neoplastic diseases (group 1-108 subjects) with a group of patients with other types of effusions (group 2-63 subjects). They compared data in the case-history, physical examination, examination of the effusions and other auxiliary examinations. For significantly different parameters of blood examination (CEA, TPA, IgM, LDH) and the effusions (CEA, IgM, ALP) liminal values, specificity and sensitivity were assessed for differentiation of tumourous and other types of exudates. The authors compared also the required time and method of diagnosis in the two groups of patients. In group 1 cytology of the exudate, biopsy of the pleura and bronchoscopy were most valuable. In patients of group 2 in addition to the cytology of the exudate, biochemistry and bacteriology and auxiliary examinations were most important. The number of necessary diagnostic "steps" for assessment of the aetiology of exudates differed. Fewer steps were necessary for assessment of tumourous exudates. The groups differed as to treatment and survival of the patients.
Keywords: Humans; Adolescent; Diagnosis, Differential; mladiství; Middle Aged; Adult; senioři; Aged; dospělí; diferenciální diagnóza; lidé; pleurální výpotek; Pleural Effusion; lidé středního věku